Topographic Organization and Corticocortical Connections of the Forepaw Representation in Areas S1 and SC of the Opossum: Evidence for a Possible Role of Area SC in Multimodal Processing. - Renata Figueiredo Anomal; Vanessa eRocha-Rego; João G Franca (Frontiers Media S.A., 2011)
In small-brained mammals, such as opossums, the cortex is organized in fewer sensory and motor areas than in mammals endowed with larger cortical sheets. The presence of a multimodal field, involved in the integration of sensory inputs has not been clearly characterized in those mammals. In the present study, the corticocortical connections of the forepaw representation in the caudal somatosensory area (SC) of the Didelphis aurita opossum was studied with injections of fluorescent anatomical tracers in SC. Electrophysiological mapping of S1 was used to delimit its respective rostral and caudal borders, and to guide SC injections. The areal borders of S1 and the location of area SC were further confirmed by myeloarchitecture. In S1, we found a well-delimited forepaw representation, although it presented a crude internal topographic organization. Cortical projections to S1 originate in somatosensory areas of the parietal cortex, and appeared to be mostly homotopic. Physiological and connectional evidence were provided for a topographic organization in opossum area SC as well. Most notably, corticocortical projections to the forepaw representation of SC originated from somatosensory cortical areas and from cortex representing other sensory modalities, especially the visual peristriate cortex. This suggests that SC might be involved in multimodal processing similar to the posterior parietal cortex of species with larger brains.